Balancing Microglial Density and Activation in Central Nervous System Development and Disease - Shunqi Wang; Liangjing Pan; Chong Sun; Chaolin Ma; Haili Pan (Current Issues in Molecular Biology)
Microglia, the resident immune cells of the central nervous system, play multifaceted roles in both health and disease. During development, they regulate neurogenesis and refine neural circuits through synaptic pruning. In adulthood, microglia maintain homeostasis and dynamically respond to pathological insults, where they contribute to responding to neuroinflammatory challenges. This review summarizes microglial contributions to neurodevelopment and also outlines their function across various neurodegenerative diseases, such as Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, and amyotrophic lateral sclerosis, highlighting both protective and detrimental effects. Finally, recent advances in microglial-targeted therapies and lifestyle-based interventions are highlighted, underscoring the translational potential of modulating microglial states. Elucidating the dual roles of microglia in development and disease could guide the design of therapeutic strategies aimed at enhancing neuroprotection while minimizing neurotoxicity.